Banco de semillas de arvenses en plantaciones forestales de Tectona grandis L.f. (TECA) de tres zonas del trópico húmedo Ecuatoriano. - Armijos Loor, Yuliza Deyanira (2019)
The present study was carried out in plantations of Tectona grandis L.f. (teak) of different ages, belonging to the cantons Palenque, Balzar and Pichincha, where 120 soil subsamples were extracted from 24 sampling units from 6 different sites with the intention of analyzing the weed seed bank. Each soil sample was placed in germination bands and some greenhouse conditions, to accelerate germination and prevent contamination, then the affected seedlings suitable for identification were counted by species, subsequently removed. Using the data obtained, the density and composition of the seed bank, the importance value index, the diversity and the similarity between sites was calculated. A total of 4031 seeds were determined, where 83 species, 38 families and 67 genera were identified. The estimated density ranged between 26,55 and 88,36 million seeds / ha. The composition of the SSB was mainly of herbs (95,04%), dicotyledonous (51,73%), native (86,46%), annual (59,45%) and the dispersion that stood out was hydrochloric (42,76%) On the other hand, the highest percentages of IVI were reported by Scirpus sp., Cyperus odoratus, Cyperus iria and Mecardonia procumbens. In all studied areas the diversity was medium according to the Shannon-Wiever index (1.73-2.91), while Simpson, a high diversity (0,72-0,91). However, La Colina, La Párraga, La Reserva and Río Grande Pichincha, reach oscillation values between 0.68 and 0.74 according to the Pielou index, where it is interpreted that there is a homogeneous abundance. Through the cluster analysis, three groups were formed according to the similarity between seed banks. Finally, the analysis of variance regarding the number of individuals revealed that there are no specific differences, so the null hypothesis (H0) was accepted. Keywords: Soil seed bank (SSB), composition, importance value index (IVI), weeds